Pembangunan model penerimaan dan penggunaan e-khidmat Awam berdasarkan utaut / Mohd Khalit Othman - Mohd Khalit, Othman (2016)
In simple words, e-Service is defined as the use of technology and electronic channels including kiosks and internet to facilitate the delivery of information and public services between government and public. In line with technological developments in the ICT era, e-Service application of Electronic Government (EG) has played a very important role in various aspects of the delivery of information and public services, particularly in the public sector and citizens. There are many studies that have examined the factors of success and acceptance of the use of e-Service (e-Service adoption factors) in general, but very less research focused on success factors for the use and acceptance in e-Service of Electronic Government (EG) or public sector (public eServices) in Malaysia. Due to the lack of research focusing on these aspects, the main objectives of this study were: i) to identify the adoption factors of Public e-Service system and the relationship between these factors, ii) to study the suitability of UTAUT model elements to the adoption behaviour of Public eService System, and iii) to develop a eService adoption model for Electronic Government (EG) or public sector. Adoption factors of this model can be identified through the literature study and findings of the analysis from research data. UTAUT theory has been applied in this research as a research theory while quantitative methodologies have been used as a research approach by involving the measurement of data using Likert scale from 1-7, where a set of questionnaires as the main instrument to collect data. Besides that, the method of deductive and inductive reasoning also used in this study especially for generating hypotheses. In total, there are 5 main phases in this study. The first phase is preliminary investigation analysis involving problem definition, document analysis and review of previous studies. The second phase is a pilot studies that involving the construction and management of a questionnaires set. The third phase is the phase of data collection based on a questionnaire technique to get the adoption factors of Public eService. A total of 436 set questionnaires were successfully collected from over 1000 respondents for analysis using SPSS IBM package, version 21. The fourth phase is the phase of data analysis using SPSS package. Data analysis that was done such as an exploratory factor analysis (EFA) to get the value of KMO and Bartlett's Test; reliability analysis to get Alpha Cronbach value; frequency analysis to obtain the mean value and standard deviation; normality and correlation analysis as well as goodness of fit analyisis for verification hypotheses by using analysis test of Kruskal Wallis statistics to see the chi-square value and p-values (Sig. value). The fifth phase which is model testing/verification phase and the presentation of study reports. Model testing/verification is using a mathematical formulation by using mathematical induction. The results from this proving, shown that the mathematical model for proposed model which is E  XeKhidmat is true for i  1,2,  ,11 where i e is the building blocks for E that is ei is element for E that representing ‘adoption factors of the public eService’ and XeKhidmat represents ‘acceptance and use of the public eService system’. The findings from the data analysis shown research instrument is very reliable with the value of Cronbach’s alpha > 0.9, instrument item are factorable with the value of Bartlett's Test > 0.75 and the sample size is large enough to produce results/possible solutions (with the value of KMO > 0.7) and there is a significant relationship between research model elements with the hypothesis testing and correlation values for each vii element of the model were above .35**. The result of all these values have suggested that elements of the proposed research model that was developed in this study are acceptable. In addition, the results from data analysis and model testing/verification by using mathematical induction techniques have shown that; i) there are 11 factors that affect the adoption of public eService for Electronic Government (EG), ii) research model is valid and fit with 11 elements as success factors of the adoption of the public eService system and iii) the use of UTAUT theory is appropriate and can be used/applied in Malaysia environments to look at the factors that influence (the successful) the adoption of the public eService system. The main contribution of this research is the development of the adoption model of the public eService for Malaysia Electronic Government (EG) that consists of 11 key elements as adoption factors of the public eService, namely as the cooperation and support, social and cultural awareness, trustworthiness/usability of ICT , user characteristic, service quality, customer satisfaction, system design/web, ICT infrastructure, government commitment, legislation and policies, and the influence of top management. This research has also shown that UTAUT theory can be used/applied to look at the adoption factors of public eService in Malaysia. In addition, this research will add the information knowledge (finding) by filling the gaps of the literature review, particularly relevant with the adoption of the public eService system for e-government in Malaysia.